COVID-19 and resilience innovations in food supply chains: Two years later - Reardon, Thomas; Swinnen, Johan; Vos, Rob (International Food Policy Research Institute, 2022)
Two years after the start of the COVID-19 pandemic, food value chains have undergone some remarkable adjustments, evolving to meet rapidly changing conditions. Their capacity to make these adjustments has depended on public investments in the logistics infrastructure and wholesale markets that form the structure of food systems, as well as public policies that facilitate efficient exchange and private sector innovations, the flow of food systems.